Simbolismo y evolución del significado del arte religioso en la iglesia de san francisco analizado desde el postmodernismo - Castro Tafur, Juan Sebastián (2014)
In search of divinity always was human being history in different religions. They have built their mystic culture for transmitting a religion idea. Catholic religion is known as grandly of artistic formation in Quito city. In this years the institution has charged of creating producing an distributing a lot of building plastic about religion. San Francisco church, receives a lot of building plastic in Ecuador and in the world. These artistic expressions were built in specific situations. In specific situations, they permit to transmit a message.